Socio-Physical and Environmental Evaluation of Courtyard Space and Courtyard-Lifestyle in the Context of Swahili Architecture and Culture-Case Study of Dar es Salaam, Tanzania - Ombeni Swai (International Journal of Architectural Engineering Technology, 2017)
This study was meant to analyze courtyard space in Magomeni neighborhood, which comprises Swahili architectural buildings arranged in grid iron pattern built in 1940s as African settlement. Three field surveys were conducted in 2012, 2013 and 2014 where, 99, 100 and 99 households samples were consecutively picked up for spatial, social, environmental and cultural analysis. In each survey, courtyard spaces were studied based on previous functions in terms of physical, environmental and socio-spatial roles in the Swahili architecture and lifestyle of the people. The original intended role of courtyard spaces were analyzed and compared with the current situation where most of them have lost their functions (architectural, environmental, cultural and social) due extension of rooms in the courtyard spaces which is caused by urbanization and socio-economic needs for renting spaces in areas within a walking distance from the city center. The physical analysis was followed up by the socio-statistical investigation where the results from the two analytical methods were discussed with the results as follows: Pragmatically, the courtyard spaces in Swahili architecture had central role in the physical, environmental and social layout of buildings which in this study it is considered as a “center of life” or genius loci of the Swahili architecture. The alteration in most of the buildings by extending rooms into the courtyard space has caused a downfall of this very vital space which has resulted into change of lifestyle of the residents. Discomfort due to lack of cross ventilation was reported by most of the respondents. Consequently, there is an excessive demand for artificial cooling and ventilation appliances which has increased the cost of living in the neighbourhood. Although residents have shown some efforts to plant trees to improve the living condition, a holistic approach from both the government and the community is needed in the redevelopment of the neighbourhood.